WORK IN RURAL AREAS, AN ANALYSIS OF THE UNEMPLOYMENT RATE AND ITS EVOLUTION OVER THE LAST DECADE - Sarina ROSENBERG; Dragos CRISTEA; Mihaela NECULIȚĂ; Ira-Adeline SIMIONOV; Ștefan-Mihai PETREA; Alina MOGODAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The economic reality of the Romanian rural space describes a different unemployment rate than those registered in the urban areas or at national level. At the same time, the dynamics of the economic sectors belonging to the rural areas is different from its evolution in the urban environment. Forms of employment in rural areas tend to be predominantly of a permanent nature, to the detriment of temporary work or seasonal ones. Elements of influence on the individual, which affect the decision to work or the option to choose a satisfactory job are the financial and social conditions. Influencing factors such as the level of education and qualification, the level of income per person or household, the work seasonality phenomenon in different economic sectors, constantly change the employment work level, also the contractual form in which the work is performed. This article describes the interaction of some economic and social indicators on the unemployment rate in the Romanian rural areas and highlights its evolution in the economic and social context of the last decade. The analysis method used in this paper is the quantitative one. An important share of the total number of unemployed in rural areas, is represented by people who have never worked, who have never had a work experience, regardless of age or level of education. The highest values are registered for people aged between 15-24 years and for those who graduated high school and the lowest weight values are for people aged 55-64 years and those with university degrees. For the last decade, the highest number of rural unemployed are people who have finished or graduate the high school, and the unemployed with secondary school. The highest increasing value of unemployed people is recorded in 2015. The highest decreasing values of unemployed people are recorded between 2016 and 2019.